Kontrak Pembiayaan Murabahah Serta Aplikasinya dalam Masyarakat Ditinjau dari Perspektif Fiqh Muamalah Maliyah - Arpizal Arpizal; Sri Sudiarti; Asmaul Husna (Yayasan Rahmat Islamiyah, 2021)
The implementation of Islamic economics has recently been increasingly recognized by various layers of society, coupled with the presence of the Indonesian Islamic Bank (BSI) which strengthens Islamic values. The implementation of sharia economics is an alternative that can be chosen by people who want every muamalah that is carried out free from elements that are prohibited by Islamic law. Muslims in Indonesia are increasingly aware that the element of muamalah, especially in the economic field, must be based on Islamic law so that every transaction or act gets the pleasure of Allah swt and acts of worship. Such as murabahah contracts, including the most widely used by Muslim communities in Indonesia. The contract is widely used in Islamic banking to transact with its customers. However, outside of Islamic banking, there are also individuals who apply murabahah contracts, although the numbers are small. Implementation by sharia banking and individual communities must remain in accordance with the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The DSN-MUI fatwa has explained the terms and pillars of each.Keywords: Akad, Murabahah, Application, Fiqh Mualamah Maliyah